Detection of Quinolone Resistance Genes of Klebsiella pneumoniae Isolated from Patients with Urinary Tract Infection attending Some Selected Hospitals in Irbid, Jordan - Idris, S.L.; Shboul, S.A.; Dabo, N.T. (UMYU Journal of Microbiology Research)
The incidence of resistant clinical bacteria associated with urinary tract infection (UTI) has been on the increase worldwide. Urinary tract is the most common site of infection for Klebsiella spp. Clinical isolates of fluoroquinolone-resistant Enterobacteriacea are emerging worldwide. The present study was designed to detect the presence of quinolone resistance genes: Chromosome and Plasmid mediated genes (PMQR) in Klebsiella pneumoniae isolated in patients attending some selected hospitals in Irbid, Jordan. One hundred and twelve isolates (112) of K. pneumoniae were collected from patients diagnosed with UTI from cultures available at the Microbiology laboratory at King Abdullah University Hospital (KAUH), Princess Basma Hospital, Prince Rashed Hospital and King Hussein Medical center between January 2014-June 2014. The bacterial isolates were identified as K. Pneumoniae morphologically and biochemically. Kirby-Bauer disk diffusion method was used to test the antimicrobial susceptibility to the fluoroquinolone antimicrobial agents: Ciprofloxacin, Ofloxacin, Norfloxacin, Lomefloxacin, Levofloxacin, Enoxacin, Moxifloxacin and Gatifloxacin. Conventional polymerase chain reaction (PCR) with specific primers to the fluoroquinolone genes was carried out to detect the presence of the genes: gyrA, parC, aac (6′)-Ib- cr and qepA. Sequencing of the positive strains for the quinolone resistance genes was carried out to determine the nucleotide sequence and compare it with the nucleotide sequence of the reference strains. Plasmid profile was conducted to relate the number and size of plasmids with antimicrobial resistance pattern of the isolates. Antimicrobial resistance ranged from 23.2% for Levofloxacin and Enoxacin to 28.6% for Moxifloxacin. Out of the 38 resistant isolates 19(50 %) expressed the PMQR gene aac (6′)-Ib- cr, none of the isolates expressed the efflux pump PMQR gene qepA, 5(13 %) expressed gyrA and 6(16 %) expressed parC chromosome genes. Plasmid profile of PMQR positive and negative strains showed plasmids with the same size (23,130bp). Nucleotide sequence of genes of positive strains in our study showed high percentage of identity with sequence of the reference strains. The most effective fluoroquinolones against urinary tract K. pneumoniae the isolate is Enoxacin, Levofloxacin and Ofloxacin. Our study found high prevalence of the PMQR gene aac (6′)-Ib-cr in the urinary K. pneumoniae (50%), this is alarming as the genes are located on plasmid which could be easily transferred by conjugation.